FACTORS AFFECTING PROFITABILITY ON BANKING COMPANIES LISTED ON THE IDX - Melvina , Melvina; Ekadjaja, Agustin (International Journal of Application on Economics and Business, 2023)
This study aims to obtain empirical evidence about the effects of Capital Adequacy Ratio (CAR), Non-Performing Loan (NPL), Net Interest Margin (NIM), Current Account Saving Account (CASA), and Operating Expenses to Operating Income (BOPO) on the profitability of banking companies listed on the Indonesia Stock Exchange (IDX) in 2017-2020. This research uses 27 banking companies selected using purposive sampling method. The research data will be processed using the EViews 9.0 program. The results of this research indicate that the NIM has a positive and significant effect on profitability, BOPO has a negative and significant effect on profitability, while CAR, NPL, and CASA have no significant effect on profitability.